Standardizing Septocolumellar Sutures: A New Practical Classification - Apaydin, Fazil; Capelleras, Marta; Saghir, Meshari (Facial Plastic Surgery, 2023)
The septocolumellar sutures are very helpful to obtain planned rotation and projection. The goal of this study is to revitalize the septocolumellar techniques described before and present an easy new classification for these sutures, and to present their multiple uses on the same patient as a new option for surgeons. Eighty patients were involved in this retrospective study. All the patients were females except one. A detailed preoperative preparation was performed on all patients by following the principles of precision profileplasty. In this study, five main types of septocolumellar sutures were used. Type 4 septocolumellar suture was used in 39 cases, type 3 in 33, type 2 in 22, type 1 in 5, and type 5 in 2 cases. In 21 cases, more than one suture was used. In conclusion, the new practical classification presented in this study gives the surgeon powerful tools to reshape the tip during surgery.
Keywords: septocolumellar suture; projection; rotation; tip surgery